The impact of IFRS on industry - Lavi, Mohan R. (Wiley, 2016)
Opening with an overview of IFRS, including a summary of all the standards, the book goes on to provide detailed coverage of the standards that can impact all industries, including IAS-40, IFRS 1, and IFRS 5. Thereafter, it offers practical advice and guidance on the application of IFRS in specific industries, including automotive; oil and gas; bio-sciences; infrastructure; airlines; media and communications; government-owned entities; mining; software; banking and financial services; insurance; FMCG; shipping; pharmaceuticals; telecoms; real estate and construction; power; SMEs; retail; e-commerce; and the service sector. The book concludes with a discussion on the collateral impact of implementing IFRS and how forthcoming IFRS Standards could impact specific industries.